Quantitative sensory response of the SCM muscle on sustained low level activation simulating co-contractions during bruxing - Eberhard, Lydia; Pfau, Doreen (Archives of oral biology, 2018)
Objective: Bruxism is discussed as an etiological factor in the pathogenesis of orofacial and cervical pain. As the sternocleidomastoid muscle (SCM) is co-activated during clenching, our aim was to investigate, whether the muscle loading leads to peripheral or central sensitizations. Design: In twenty-one healthy female volunteers, somatosensory proﬁles of the SCM were recorded according to the test battery of the German Research Network on Neuropathic Pain (DFNS) prior to and after an isometric muscle exercise. QST comprised thermal and mechanical stimuli. A submaximal activation of the SCM (15% MVC) was kept for 10 min in sitting position. In separate test sessions one month apart, one sham and one verum experiment were conducted in randomized order. During the muscle loading, the parameters cold detection threshold (CDT), mechanical pain sensitivity (MPS) and pressure pain treshold (PPT) were tested and experimental pain recorded by visual analogoue scales (VAS). All test sessions were performed during the follicular phase of the menstrual cycle (day 5), to avoid eﬀects on pain perception. Data were analyzed with Repeated Measures ANOVA (SPSS 22.0). Results: No signiﬁcant changes were found during or after (sham) loading except for stimulus-response-function (SR, P = 0.01) and PPT (P = 0.02) in the sham test. No eﬀect was observed in the verum experiment (P = 0.12 up to 1.0). Conclusion: Prolonged low level contraction of the SCM does not evoke painful sensitization. In contrast, submaximal muscle activation seems to have a protective eﬀect corresponding to a training eﬀect preventing sensitization.